The N-Formyl Peptide Receptors and Rheumatoid Arthritis: A Dangerous Liaison or Confusing Relationship? - Mormile, Ilaria; Rossi, Francesca Wanda; Prevete, Nella; Granata, Francescopaolo; Pucino, Valentina; de Paulis, Amato (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by a progressive symmetric inflammation of the joints resulting in bone erosion and cartilage destruction with a progressive loss of function and joint deformity. An increased number of findings support the role of innate immunity in RA: many innate immune mechanisms are responsible for producing several cytokines and chemokines involved in RA pathogenesis, such as Tumor Necrosis Factor (TNF)-α, interleukin (IL)-6, and IL-1. Pattern recognition receptors (PRRs) play a crucial role in modulating the activity of the innate arm of the immune response. Herein, we focused our attention over the years on the expression and functions of a specific class of PRR, namely formyl peptide receptors (FPRs), which exert a key function in both sustaining and resolving the inflammatory response, depending on the context and/or the agonist. We performed a broad review of the data available in the literature on the role of FPRs and their ligands in RA. Furthermore, we queried a publicly available database collecting data from 90 RA patients with different clinic features to evaluate the possible association between FPRs and clinic-pathologic parameters of RA patients.